Pengaruh Struktur Modal, Mekanisme Bonus dan Tunneling Incentive Terhadap Agresivitas Pajak - Putri Rahayu; Imar Halimah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to examine and obtain empirical evidence regarding the effect of capital structure, bonus mechanisms, and tunneling incentives on tax aggressiveness. The study uses a sample of companies in the industrials sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The sampling technique employed is purposive sampling, in which 16 companies were selected from a total of 65 industrial sector companies over a five-year period, resulting in 80 observations. The data were analyzed using panel data regression with the Fixed Effect Model (FEM), and processed using EViews 13 software. And the results indicate that capital structure, bonus mechanisms, and tunneling incentives simultaneously have a significant effect on tax aggressiveness, with an F-statistic value of 2.298416 and a probability of 0.008304 (< 0.05). Partially, capital structure has a coefficient value of 0.101099 with a probability of 0.0583 (> 0.05), indicating that it does not have a significant effect on tax aggressiveness. The bonus mechanism has a coefficient value of −0.023118 with a probability of 0.2315 (> 0.05), indicating that it does not have a significant effect on tax aggressiveness. Meanwhile, tunneling incentive shows a coefficient value of 0.320027 with a probability of 0.0253 (< 0.05), which indicates that tunneling incentive has a positive and significant effect on tax aggressiveness.